Audiotactile interaction can change over time in cochlear implant users - Landry, Simon P.; Guillemot, Jean-Paul; Champoux, François (Frontiers in Human Neuroscience, 2014)
Recent results suggest that audiotactile interactions are disturbed in cochlear implant (CI) users. However, further exploration regarding the factors responsible for such abnormal sensory processing is still required. Considering the temporal nature of a previously used multisensory task, it remains unclear whether any aberrant results were caused by the specificity of the interaction studied or rather if it reflects an overall abnormal interaction. Moreover, although duration of experience with a CI has often been linked with the recovery of auditory functions, its impact on multisensory performance remains uncertain. In the present study, we used the parchment-skin illusion, a robust illustration of sound-biased perception of touch based on changes in auditory frequencies, to investigate the specificities of audiotactile interactions in CI users. Whereas individuals with relatively little experience with the CI performed similarly to the control group, experienced CI users showed a significantly greater illusory percept. The overall results suggest that despite being able to ignore auditory distractors in a temporal audiotactile task, CI users develop to become greatly influenced by auditory input in a spectral audiotactile task. When considered with the existing body of research, these results confirm that normal sensory interaction processing can be compromised in CI users.